PENGARUH MOTIVASI, ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB), DAN KOMITMEN TERHADAP PRESTASI KERJA PEGAWAI PADA BAGIAN UMUM SEKRETARIAT KABUPATEN PAMEKASAN - jurnalmap map; Qamarudin ÔÇÄ; Muninghar ÔÇÄ; Fatimah Riswati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
The population in this study is all employees in the General Section of the Regional Secretariat of Pamekasan Regency with a total sample of 64 people. The purpose of this study is 1) To describe about the motivation, organizational citizenship behavior, commitment and performance of employees, 2) To test and analyze whether the motivation, organizational citizenship behavior and commitment affect simultaneously on employee performance, 3) To test and analyze the motivation to influence the work performance of employees, 4) To test and analyze the effect of OCB partially on employee performance, 5) To test and analyze the effect of commitment partially on employee performance. The results showed that simultaneously, motivation, OCB and commitment had significant effect on employee performance. Partially, motivation, OCB and commitment have a significant effect on employee performance. OCB variables have a dominant influence on employee performance in the general section of the district secretariat pamekasan. Keywords: motivation, OCB, commitment, job performance